PENGARUH BUDAYA ORGANISASI DAN PELATIHAN TERHADAP KINERJA GURU PNS DI SMA NEGERI 5 MODEL LUBUKLINGGAU - Surajiyo Surajiyo (LPPM UNIVERSITAS BINA INSAN, 2020)
This study aims to see the influence of Organizational Culture and Training on Teacher Performance in SMA Negeri 5 Model Kota Lubuklinggau. The number of research samples was 30 people taken from all teachers. The results of the study have a simultaneous impact: (a) First Hypothesis (H1) the influence of Culture on Teacher Performance in SMA Negeri 5 Model Kota Lubuklinggau, the results of the study indicate that Organizational Culture partially affects Teacher Performance in SMA Negeri 5 Model Kota Lubuklinggau. (b) Hypothesis II (H2) i The Effect of Training on Teacher Performance in SMA Negeri 5 Model Kota Lubuklinggau. And the calculation results obtained t value of 5.542 while the value of t table with a = 5% df (n-2) = (30-2) i is 1.701, t count> t table then Ho is rejected and Ha accepted. (c) The third hypothesis (H3) is the Influence of Organizational Culture and Training on Teacher Performance in the Model SMA Negeri 5 Lubuklingau City. The results showed that Organizational Culture and Training simultaneously had an effect on Teacher Performance in SMA Negeri 5 Kota Model Lubuklinggau. With the value of R squere (R2) the result of the analysis is the value of 0.812 (81.2%). And from the test results obtained the value fcount of 21,281. With a significant level of 0.000, and a = 5% and the numerator (k = 2) is the fable of 3.35 fcount> ftable then Ho is rejected and Ha is accepted. This means that there is a significant influence between organizational culture and training on teacher performance in SMA NEGERI 5 Model Kota Lubuklinggau.